Comparative Study of Thermophilic Microorganisms in Hot Springs of Varai-Sativali, Thane District, Maharashtra (India) (International Journal of Food and Nutritional Sciences, 2022)
Thermophilic microorganisms found in hot springs are known for their ability to produce thermostable enzymes with significant industrial applications. This study investigates the thermophilic bacterial diversity and enzymatic potential in the Varai-Sativali hot springs of Thane district, Maharashtra. A total of 12 bacterial strains were isolated from samples collected from the hot springs, and their extracellular enzyme production, including gelatinase, urease, amylase, cellulase, and catalase, was assessed. The isolates exhibited remarkable enzymatic activity at high temperatures, indicating their potential as sources of industrially important enzymes